Relying on Faith: Spiritual Coping Experiences Among Mothers Caring for Children with Cancer - Kusumawati, Dwi Arsinta; Asyanti, Setia (Universitas Muhammadiyah Surakarta, 2025)
Caring for a child with cancer can cause profound psychological and emotional stress for mothers. Spiritual coping is often used as a strategy to manage such challenges. This research aims to describe how Muslim mothers employ spiritual coping while caring for children with cancer. A descriptive qualitative approach was used. The informants were three muslim mothers who had cared for, or were currently caring for, children with cancer. Data were collected through semi-structured interviews in the area formerly known as Surakarta Residency and analyzed using Miles and Huberman’s interactive model. Credibility was ensured through member checking, and transferability was supported by detailed description techniques. The results indicated that the informants engaged in spiritual coping by relying on Allah in three domains: behavioral practices, emotional regulation, and cognitive reframing. Family encouragement and religious beliefs influenced their choice of coping strategies. These findings suggest that incorporating spiritual coping approaches into psychosocial interventions may help mothers achieve greater inner peace in facing the challenges of childhood cancer.